Increasing father involvement in child care: What do we know about effects on child development? - Pia S. Schober (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The time fathers spend and the activities they perform with children have risen continuously in most Western countries. Increasing father involvement in child care has also been an explicit policy objective with many European countries implementing individual parental leave entitlements for fathers. Whereas these policies mainly aimed at facilitating reconciliation of market work and family care and promoting maternal employment, consequences for child development have received less attention in the policy debate. This DIW Roundup describes potential mechanisms how increased father involvement in child care may impact children's development in different domains and provides an overview of the existing empirical evidence. Overall, previous studies generally point to some moderate positive effects of fathers involvement, in particular when father-child-activities and -relationships are stimulating and of high quality and distinct from mother-child activities or maternal parenting styles.
Keywords: 330